Dynamin-related protein 1 deficiency accelerates lipopolysaccharide-induced acute liver injury and inflammation in mice - Lixiang Wang (Nature Portfolio, 2021)
Wang et al. report that deficiency of dynamin-related protein 1, which controls mitochondrial fission, accelerates lipopolysaccharide-induced acute liver injury and inflammation in mice. Thus, they highlight mitochondria dynamics dysfunction as a new mechanism of liver disease development.